2001
DOI: 10.1074/jbc.m100240200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Slit Protein Interactions with Glypican-1

Abstract: We have demonstrated previously that the Slit proteins, which are involved in axonal guidance and related developmental processes in nervous tissue, are ligands of the glycosylphosphatidylinositol-anchored heparan sulfate proteoglycan glypican-1 in brain (Liang, Y., Annan, R. S., Carr, S. A., Popp, S., Mevissen, M., Margolis, R. K., and Margolis, R. U. (1999) J. Biol. Chem. 274, 17885-17892). To characterize these interactions in more detail, recombinant human Slit-2 protein and the N-and C-terminal portions g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 35 publications
6
96
0
Order By: Relevance
“…In vertebrates, GPCs are predominantly expressed during nervous system development, where they serve as guidance cues for axonal navigation and neuronal migration. Consistent with the role in axon guidance, GPCs also interact with the axon guidance molecule Slit (15,16). Moreover, they regulate several signaling pathways, including the Wnt, Hedgehog, fibroblast growth factor, and bone morphogenic protein pathways (17).…”
mentioning
confidence: 76%
“…In vertebrates, GPCs are predominantly expressed during nervous system development, where they serve as guidance cues for axonal navigation and neuronal migration. Consistent with the role in axon guidance, GPCs also interact with the axon guidance molecule Slit (15,16). Moreover, they regulate several signaling pathways, including the Wnt, Hedgehog, fibroblast growth factor, and bone morphogenic protein pathways (17).…”
mentioning
confidence: 76%
“…Thus, biochemical experiments have shown that Slits bind the heparan sulfate proteoglycan glypican-1 (Liang et al, 1999;Ronca et al, 2001). Heparan sulfate enhances the affinity of Slit2 for Robo1 receptors in vitro, and removal of cell surface heparan sulfate by heparinase III treatment or addition of saturating amounts of heparan sulfate abolishes the repulsive activity of Slit2 toward olfactory bulb axons in explant cultures (Hu, 2001).…”
Section: Interaction Of Slit/robo Signaling With Other Moleculesmentioning
confidence: 99%
“…Several midline glial specializations such as the roof and floor plates and the chiasmatic glial palisade express slit (Erskine et al 2000 and that may occur in the presumptive derivatives of the midbrain homologues in culture. There is also convincing evidence that glypican-1 binds slit (Liang et al 1999, Ronca et al 2001 and there is no insurmountable obstacle to the formation of a complex of slit/ glypican and a (neuronal) robo receptor since glypican-1 is expressed by astrocytes (Bansal et al 1996) and is shed from the cell surAn Acad Bras Cienc (2002) 74 (4) face (Winkler et al 2002). Additionally, syndecans 2 and 4, that may also be shed, are heavily expressed in cultured astrocytes (Bansal et al 1996).…”
Section: Non-neuronal Hspgs Modulation Of Neurite Growth At the Midlimentioning
confidence: 99%
“…Three distinct slit genes (Slit1, Slit2 and Slit3) and three distinct robo genes (robo1, robo2 and rig-1) have been cloned in mammals. The mammalian homologues of slit are ligands of the heparan sulfate proteoglycan (HSPG) glypican-1 (Liang et al 1999, Ronca et al 2001.…”
Section: Slitmentioning
confidence: 99%